PENGARUH TINGKAT PENDIDIKAN, AKSESIBILITAS KREDIT, KEMAMPUAN MENYUSUN DAN MENYAJIKAN LAPORAN KEUANGAN, SERTA MINAT PENGGUNAAN E-COMMERCE TERHADAP KINERJA UMKM (Studi Pada UMKM di Kota Malang) - Siti Wulandari; Maslichah Maslichah; Afifudin Afifudin (Universitas Islam Malang, 2021)
The purpose of this study was to examine the significant effect of education level, credit accessibility, ability to prepare and present financial reports, and interest in using e-commerce on the performance of Micro, Small and Medium Enterprises. The population in this study is the MSME business actors in the city of Malang. Sampling was carried out as many as 99 MSME business actors. This study uses a quantitative approach, in collecting data using a questionnaire and data analysis using multiple linear analysis. The results showed that there was a significant influence between education level, credit accessibility, ability to prepare and present financial reports, and interest in using e-commerce on the performance of MSMEs in the city of Malang. Keywords : Education Level, Credit Accessibility, Financial Statements, E-commerce, MSME Performance